1993
DOI: 10.1152/jappl.1993.74.6.3046
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow velocity in humans exposed to 24 h of head-down tilt

Abstract: This study investigates cerebral blood flow (CBF) velocity in humans before, during, and after 24 h of 6 degree head-down tilt (HDT), which is a currently accepted experimental model to simulate microgravity. CBF velocity was measured by use of the transcranial Doppler technique in the right middle cerebral artery of eight healthy male subjects. Mean CBF velocity increased from the pre-HDT upright seated baseline value of 55.5 +/- 3.7 (SE) cm/s to 61.5 +/- 3.3 cm/s at 0.5 h of HDT (P < 0.05), reached a peak va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 0 publications
3
58
1
1
Order By: Relevance
“…In the present study, controlled breathing maintained end-tidal CO 2 concentrations, and so we conclude that acute Ϫ10°head-down tilting does not affect cerebral blood flow velocity. This conclusion is in agreement with Satake et al (17), who found no change in middle cerebral blood flow velocity with Ϫ6°head-down tilt by using single-photon-emission computed tomography, and at odds with Kawai et al (11), who documented increases of blood flow velocities with a similar Ϫ6°head-down tilt using transcra- Although loading of various baroreceptor populations should conceivably increase parasympathetic activity, we were unable to confirm such an increase. R-R intervals, R-R interval spectral power at the high frequency, and cardiovagal baroreflex sensitivity [assessed by the transfer function magnitude between systolic pressure and R-R interval (Table 2)] were unaffected by head-down tilt.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, controlled breathing maintained end-tidal CO 2 concentrations, and so we conclude that acute Ϫ10°head-down tilting does not affect cerebral blood flow velocity. This conclusion is in agreement with Satake et al (17), who found no change in middle cerebral blood flow velocity with Ϫ6°head-down tilt by using single-photon-emission computed tomography, and at odds with Kawai et al (11), who documented increases of blood flow velocities with a similar Ϫ6°head-down tilt using transcra- Although loading of various baroreceptor populations should conceivably increase parasympathetic activity, we were unable to confirm such an increase. R-R intervals, R-R interval spectral power at the high frequency, and cardiovagal baroreflex sensitivity [assessed by the transfer function magnitude between systolic pressure and R-R interval (Table 2)] were unaffected by head-down tilt.…”
Section: Discussionsupporting
confidence: 86%
“…Second, the alternative mechanism could be autoregulation of cerebral circulation. Exposure to actual or simulated microgravity elevates blood pressures in cerebral arteries [6] and veins [24,25], and increases the blood flow velocity in the middle cerebral artery [6,26,27]. These changes in hemodynamics may cause a constriction of cerebral vessels through myogenic responses [28] or changes in endothelial functions [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The factor ␣ was used to correct for the height reduction caused by the semisupine position of our bicycle ergometer with a backrest inclination of 55°(␣ ϭ sin 55°) (26).…”
Section: Subjectsmentioning
confidence: 99%